Seaweed Fly Larvae Cultivated on Macroalgae Side Streams: A Novel Marine Protein and Omega-3 Source for Rainbow Trout - Niklas Warwas; Emma L. Berdan; Xintian Xie; Elisabeth Jönsson; Jonathan A. C. Roques; Darragh Doyle; Markus Langeland; James Hinchcliffe; Henrik Pavia; Kristina Sundell (Aquaculture Nutrition)
A nutritional bottleneck in salmonid aquaculture is the procurement of marine-derived compounds, such as essential amino and fatty acids, including omega-3 fatty acids, lysine, and methionine. Therefore, insects containing these compounds are highly promising as feed ingredients. The present study evaluates larvae of a “marine” insect (Coelopa frigida, the bristly-legged seaweed fly larvae, SWFL) reared on brown algae side streams as a feed ingredient for rainbow trout (Oncorhynchus mykiss). SWFL contained, on a dry matter basis, 60% crude protein (CP), 3.5% lysine, and 1.5% methionine, as well as 17% lipids, including 4% eicosapentaenoic acid and docosahexaenoic acid. Four isoenergetic (ca. 23 MJ kg−1 gross energy) and isoproteic (ca. 45% CP) feeds were evaluated in a 10-week feeding trial. The diets included a control containing 25% fish meal, a commercial reference, and two diets substituting 40% fish meal with either SWFL or partially defatted black soldier fly larvae (BSFL) meal (Hermetia illucens). SWFL-fed fish displayed higher specific growth rates (SGR) compared to BSFL-fed fish and similar SGR compared to control and reference diet-fed fish. Feed intake in SWFL-fed fish was higher than for the control and BSFL diets and similar to the reference diet. The feed conversion ratio of fish fed the BSFL and SWFL diets was higher compared to the control, suggesting lower bioavailability of both insect meals compared to fish meals. No difference in intestinal health parameters was noted between the insect diets and the control diet, indicating good intestinal health across all treatments. However, changes in electrogenic intestinal transport were observed between the SWFL and BSFL diets, illustrating the heterogeneous effect of different insect products. Overall, SWFL meal is a promising alternative marine feed ingredient, compatible with circular production systems, as it can be efficiently cultivated using marine side streams.